[EDSA in transition ; Marag Valley ; The Man with a thousand faces - Lazaro, Cheche (Quezon City Probe Productions, 1991)
Looks at the DOTC and the DPWH putting up the EDSA Ortigas interchange; situation in Marag Valley where CCP-NPA are removed; and a profile of comedian William Nepomuceno, known as man win a thousand faces.
EDSA in transition (13 min.) -- Marag Valley (19 min.) -- The man with a thousand faces (13 min.)
VHS.
Keywords: Nepomuceno, Willy; Elevated highways -- Philippines -- Manila metropolitan area; Insurgency -- Philippines -- Kalinga-Apayao.; Male impersonators -- Philippines; Roads -- Interchanges and intersections. -- Philippines -- Manila metropolitan area; Roads -- Philippines -- Manila metropolitan area; Marag Valley (Kalinga-Apayao) -- Social conditions